2009
DOI: 10.4104/pcrj.2009.00044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulmonary rehabilitation on perceptions of breathlessness and activity in COPD patients: a qualitative study

Abstract: Aim: The aim of this study was to explore, using qualitative research methods, how pulmonary rehabilitation (PR) programmes affect the experience of activity and breathlessness of people with COPD.Methods: A qualitative, interview-based approach was employed. Participants were interviewed pre-and post-PR. Data were analysed using systematic strategies informed by grounded theory methods.Results: Nine participants (three female) took part. A change in participants' perception of breathlessness and lessening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 23 publications
4
77
0
2
Order By: Relevance
“…Under supervision, people become more comfortable exerting their body and are less likely to become panicked by exertional dyspnoea (Williams et al, 2010). Chris learned to manage his panic through the classes: "The most helpful was avoiding panic attacks… It changed my outlook… I probably looked at it from the aspect 'Well, Bugger it!…”
Section: The Impact Of Pulmonary Rehabilitation For the Patient And Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Under supervision, people become more comfortable exerting their body and are less likely to become panicked by exertional dyspnoea (Williams et al, 2010). Chris learned to manage his panic through the classes: "The most helpful was avoiding panic attacks… It changed my outlook… I probably looked at it from the aspect 'Well, Bugger it!…”
Section: The Impact Of Pulmonary Rehabilitation For the Patient And Fmentioning
confidence: 99%
“…Pulmonary rehabilitation has led to improvements in health related quality of life even where no significant improvement in lung function is demonstrated (Haave et al, 2007, Camp et al, 2000. This is in part, due to the reduction in social isolation and improved opportunities for expression of 'self' (Gullick, 2008, Toms & Harrison, 2002; patients describe feelings of enhanced well-being and hope (Milne et al, 2009, O'Shea et al, 2007, have higher self-esteem and mood (Arnold et al, 2006) and, following rehabilitation, are more likely to talk about their abilities rather than their limitations (Williams et al, 2010). Pulmonary rehabilitation can lead to a change in physical appearance and in turn, body image, and creates a sense of pride, satisfaction and achievement (O'Shea et al, 2007).…”
Section: The Impact Of Pulmonary Rehabilitation For the Patient And Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall that retired Señor Pablo critiques his diminished capacity to stroll at the same pace with friends or to stop his grandchildren's hands from slipping out of his grasp and them running off. Even though some studies reveal restrictions and losses in COPD patients' emotional and social realms 13,14 , this anthropological study details the meaning of functional limitations in real life contexts. It probes what really matters 40 .…”
Section: Discussionmentioning
confidence: 99%
“…What is lacking is a dense ethnographic description of COPD as a "cultural idiom of distress" 12 . Medical anthropologists have revealed that providers' and patients' constructions of disease and illness, respectively, often contest each other 3,13,14 . In 1977, Eisenberg 15 first drew a distinction between the professional biomedical notion of disease and popular ideas of illness.…”
Section: Introductionmentioning
confidence: 99%